(untitled) (Revista GEON (Gestión, Organizaciones y Negocios), 2022)
Problematic: Competitiveness in the market follows a growing trend due to global phenomena that have implications for the organizational scenario. In this context, organizational communication comes into play as a tool for adapting to these changes. Although there are important studies on the subject, the favorable impact of organizational communication is still not fully recognized in many countries. In that way, it’s necessary to continue to deepen and delimit the field of study. Objectives: Analyse the importance of both internal and external communication to identify strategies that can be used as a competitive differentiator for the company. Materials and methods: This is exploratory research with a qualitative approach through a structured and rigorous review of high-impact articles, academic repositories, among others. Results: The results show that there is little research on the subject carried out in our region, mainly from European and Asian countries; furthermore, most of the scientific articles taken as primary sources are of the Q1 and Q2 category. On the other hand, the number of articles on the subject has increased after COVID-19 confinement. Discussion: It became evident that communication is indeed a strategic management tool that influences brand positioning through competitive differentiation, thus contributing to the co-creation of values in all contexts and with the different stakeholders. Conclusions: Communication in its various dimensions is a priority for optimal organizational development and, due to the pandemic, is taking on the challenge and responsibility to redefine itself. Contribution/originality: It is hoped to continue contributing to the field of study and to generate proposals aimed at improving organizational communication in any type and size of the company.